The Biography of Gruffudd AP Cynan: Literary Form and Historical Interpretation. (1st June 2019) - Smith, Beverley
This article examines the thirteenth- century Welsh translation of the biography of Gruffudd ap Cynan alongside the Latin text derived from the original Vita of twelfth-century composition, first published in 2005, so as to study the manner in which the classical form of second-century origin used by Suetonius for his Lives of the Caesars was adapted to the needs of a biography of a medieval Christian king. The work of an unidentified author, its composition is attributed to a period of tension in the dynasty of Gwynedd during the reign of Owain Gwynedd (d. 1170). The study closes with a consideration of the way in which significant themes in the account of the deeds of Gruffudd in the Vita are reflected in the dynastic policy of the princes of Gwynedd during the generations of princely rule terminated by thirteenth-century conquest.